XPERT MYCOBACTERIUM TUBERCULOSIS/RIFAMPICIN ASSAY: A BOON IN TUBERCULOSIS DIAGNOSTICS - Ramamurthy, Kavya; Bhat, Sevitha; Shenoy, Shalini; Rangnekar, Aseem (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Mycobacterium tuberculosis (MTB) remains one of the most significant causes of mortality and morbidity in developing countries especially India. India has the highest burden of TB, with an estimated incidence figure of 2.1 million cases out of the 9 million cases of TB globally. Diagnosis of TB relies on conventional microscopy and culture with drawbacks related to sensitivity, specificity, turn around time (TAT). The aim of this study was to evaluate the performance of Xpert MTB/rifampicin (RIF) assay (GX) for MTB detection in pulmonary and extrapulmonary clinical samples. Methods: A total of 209 clinical specimens (182: pulmonary and 27: extrapulmonary) were processed using auramine smear, culture by mycobacteria growth indicator tube and GenXpert. Results: The sensitivity of GenXpert was 62.63% for pulmonary and 55% for extrapulmonary samples. The sensitivity and specificity of GX were 100% for the smear positive cases. The sensitivity, specificity, positive predictive value, and negative predictive value of the GX for smear negative cases were 67.8%, 97.5%, 90.4%, and 89.6%, respectively. RIF resistance was detected in 3.8% the samples. Conclusion: GenXpert, with short TAT, high sensitivity, specificity and less technical expertise required is a promising tool in TB diagnostics for the future. Keywords: GenXpert, Tuberculosis diagnosis, Molecular method, Rifampicin resistance.